2016
DOI: 10.1103/physrevb.94.064102
|View full text |Cite
|
Sign up to set email alerts
|

Role of composition, bond covalency, and short-range order in the disordering of stannate pyrochlores by swift heavy ion irradiation

Abstract: A 2 Sn 2 O 7 (A = Nd, Sm, Gd, Er, Yb, and Y) materials with the pyrochlore structure were irradiated with 2.2 GeV Au ions to systematically investigate disordering of this system in response to dense electronic excitation. Structural modifications were characterized, over multiple length scales, by transmission electron microscopy, x-ray diffraction, and Raman spectroscopy.Transformations to amorphous and disordered phases were observed, with disordering dominating the structural response of materials with sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
63
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 68 publications
2
63
1
Order By: Relevance
“…Pyrochlore materials show clear compositional trends in radiation tolerance. Like the lanthanide sesquioxides, cation ionic radii are the primary determinant of these trends [28,[95][96][97][98]. For pyrochlore materials the ratio of the A-and B-site cation radii, r A /r B , governs radiation tolerance.…”
Section: Radiation Effects In Structurally-related Lanthanide Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pyrochlore materials show clear compositional trends in radiation tolerance. Like the lanthanide sesquioxides, cation ionic radii are the primary determinant of these trends [28,[95][96][97][98]. For pyrochlore materials the ratio of the A-and B-site cation radii, r A /r B , governs radiation tolerance.…”
Section: Radiation Effects In Structurally-related Lanthanide Oxidesmentioning
confidence: 99%
“…This indicates that doping of CeO 2 with additional cations, particularly smaller transition metal elements, such as the fission frag-ments found in nuclear fuels and nuclear wastes, might reduce the radiation tolerance of this material. This doping, if sufficiently extensive, could make accessible irradiation-induced phase transformation pathways to amorphous phases, as well as short-range structural modifications resulting from local defect ordering [97,[100][101][102]. Thus, deviation from the ideal CeO 2 chemical composition due to the introduction of other atomic species appears likely to have a deleterious effect on radiation tolerance in this system.…”
Section: Radiation Effects In Structurally-related Lanthanide Oxidesmentioning
confidence: 99%
“…The behavior of defects in pyrochlore is important for many of these applications. As such, multiple methods for introducing defects into pyrochlore have been investigated in the past, including radiation damage 18–21 , high pressure 2224 , and chemical doping 2527 . A thorough understanding of the pyrochlore crystal structure is necessary to assess the behavior of defects in the material, and how those atomic-level defects can influence bulk properties.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Er 2 Zr 2 O 7 (r A /r B = 1.39) crystallizes in the defected fluorite structure and exhibits high radiation tolerance, while Er 2 Ti 2 O 7 (r A /r B = 1.66) crystallizes in the pyrochlore structure with poor radiation tolerance. A comprehensive study of the lanthanide stannate pyrochlores, Ln 2 Sn 2 O 7 (Ln = La to Lu and Y) confirmed this trend of increasing radiation tolerance with decreasing r A /r B [12,13]. A similar analysis of the oxygen positional parameter of the O 48f site, x, compared to that for the ideal pyrochlore structure (x = 0.3125) and the ideal (non-defective) fluorite structure (x = 0.375), leads to similar conclusions regarding radiation tolerance: those oxides which exhibit x values closer to the ideal fluorite value exhibit higher radiation tolerance than those with x values closer to the ideal pyrochlore structure [1,7].…”
Section: Introductionmentioning
confidence: 69%